The Role of Family Education in Tackling Juvenile Delinquency - Shelly Alvareza Zazkia (STAI Hubbulwathan Duri, 2022)
Education has an important role for child development. This research is a field research. The focus of the research is a study of the perspectives of students of the BK UIN Raden Mas Said Surakarta Study Program related to juvenile delinquency. The alpha generation or today's youth is the generation that emerged at a time when technology was advancing very rapidly. However, the development of the digital era goes hand in hand with moral degradation. Therefore, it is important to instill family education as the first education for children. The results of the study using simple linear regression analysis showed that the effect of family education on the prevention of juvenile delinquency was indicated by the value of R = 0.440 and the magnitude of the effect was 19.4%, which was proved by R2 = 0.194 which was included in the moderate/enough category. There is a significant influence between family education on the prevention of juvenile delinquency because the family is the first education for every child. Family education is the main basis for a better future life for children. But the rest is certainly influenced by other variables because children are not always in the family, such as the environment which also has a strong influence on child development.